A laboratory assessment of the potential of different strains of the entomopathogenic fungi Beauveria bassiana (Balsamo) Vuillemin and Metarhizium anisopliae (Metschnikoff) to control Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) in stored cowpea - Cherry, A.; Abalo, P.; Hell, K. (Elsevier, 2005)
Twelve indigenous and exotic isolates of Beauveria bassiana and Metarhizium anisopliae were evaluated for their virulence and their ability to suppress populations of Callosobruchus maculatus in stored cowpea. LT50 values ranged from 3.11 to 6.12 days following immersion in aqueous suspensions containing 1×108 conidia ml−1. Indigenous isolates that had been recovered from C. maculatus were more virulent in laboratory bioassays than exotic isolates from other insects. The two isolates with the shortest LT50 values were compared in dose–response assays by immersion and by exposure to cowpea grains treated with dry conidia. In both assays B. bassiana 0362 was consistently more virulent than M. anisopliae 0351. By immersion, LC50 values on day 6 post-treatment were 9.10×104 and 7.10×105 conidia ml−1 for B. bassiana 0362 and M. anisopliae 0351, respectively. Exposure to treated grains gave LC50 values of 1.15×107 and 4.44×107 conidia g−1 grain for B. bassiana 0362 and M. anisopliae 0351, respectively. In 1 kg batches of cowpea stocked with 50 adult C. maculatus, B. bassiana 0362 at both 1×107 and 1×108 conidia g−1 grain led to significant adult mortality and reduced F1 emergence relative to untreated populations. At 1×108 conidia g−1 the effect of the fungus persisted into the F1 generation. The net reproductive rates, R0, measured 26 days after insects were released were 5.16 and 7.32 for the high and low doses compared to 9.52 for the untreated control.